A Pentacene‐based Nanotube Displaying Enriched Electrochemical and Photochemical Activities. (27th December 2018) - Kuroda, Kiyonori; Yazaki, Kohei; Tanaka, Yuya; Akita, Munetaka; Sakai, Hayato; Hasobe, Taku; Tkachenko, Nikolai V.; Yoshizawa, Michito
Abstract: Unlike previously well‐studied, acyclic pentacene oligomers, the first synthesis of a cyclic pentacene trimer with a fixed tubular conformation is reported. A short‐step synthesis starting from common pentacenequinone yielded the target molecule with a 1.5 nanometer length and a subnanometer pore. Steady‐state spectroscopic analyses revealed that the close proximity of the non‐conjugated, three pentacene chromophores allows the nanotube to display stepwise electrochemical/chemical oxidation characteristics. Furthermore, time‐resolved transient absorption measurements elucidated the generation of an excited triplet state of the nanotube, with high quantum yield reaching about 180 % through intramolecular singlet fission and a very long triplet lifetime.